Keterlibatan Disiplin dan Lingkungan Kerja terhadap Kinerja Karyawan melalui Motivasi - Muhammad Ilham Hardyansyah; Kustini Kustini (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In this era, with the era of globalization, of course, it is very necessary for quality human resources who have quality accompanied by success for the achievement of the company, of course, it cannot be separated from the quality of the employees or human resources in the company. There is a decrease in employee performance due to work discipline problems and the work environment in the company. The purpose of this study is to determine the effect of work discipline and work environment variables on worker performance through motivation on CV. APT. The study method used for data collection is by distributing questionnaires and using saturated sampling technique. The population for this study is workers at CV. APT with 52 employees. Methods for data collection using the method of distributing questionnaires. The technique for data analysis used in this study is using PLS. Work Discipline is proven to be able to provide a good contribution to the work motivation of workers, the work environment cannot prove if it can provide a good contribution to the work motivation of workers, work discipline can prove to be able to provide a good contribution to the performance of workers, Work Environment not proven to be able to make a good contribution to employee performance, work motivation is proven to be able to make a good contribution to employee performance, work discipline is not proven to be able to make a good contribution to performance through work motivation of workers, work environment is not proven to be unable to make a significant contribution good performance through the Work Motivation of the workers.